СВЕТИСЛАВ ВУЛОВИЋ О ДОМЕНТИЈАНУ (Prilozi za književnost, jezik, istoriju i folklor, 2023)
This paper focuses on the views of Svetislav Vulović, Serbian literary and theatre critic and literary historian (1847‒1898), on the work of hieromonk Domentijan, Serbian writer from the 13th century. In the paper, the author analyses the segments of Vulović’s study From Old Serbian Literature. About Serbian Biographers of the 13th Century (published in 1885) that deal with Domentijan’s work. The author’s aim was to establish to what extent Vulović relied on the results of scientific research achieved until then and what new insights his study provided.Through her analysis of the parts of Vulović’s text dedicated to Domentijan, the author of this paper established that Vulović, in keeping with his critical orientation, dedicated considerable attention and space to the writer’s biography. He draws the writer’s portrait relying on the observations of P. Ј. Šafarik; he himself tried to shed more light on some relevant details from Domentijan’s life. Analysing The Hagiography of St Sava, first of all he took an interest in the writer’s sources. He established that Domentijan mostly relied on the work of Stefan the First-Crowned dedicated to St Simeon (which inspired him to reach for more complex ideational-stylistic methods, to introduce a more pronounced element of fantasy). According to Vulović’s assessment, Domentijan outdid the older writer in a number of ways. Vulović has a very high opinion of The Hagiography of St Sava, ranking it above Sava’s and Stefan’s, as well as all the other Serbian biographies. He characterises another work by Domentijan, The Hagiography of St Simeon, as a “mere compilation”. Vulović’s observation that Domentijan, while compiling this work, relied very much on his own The Hagiography of St Sava is highly valuable.The author of this paper also studied the part of Vulović’s study dedicated to Teodosije. As could be expected, in this section of his study Vulović speaks a lot about Domentijan’s hagiography of St Sava, which was Teodosije’s main source for his eponymous work. Lj. Juhas-Georgievska particularly focuses on Vulović’s very significant conclusion that Domentijan is “more dependable” than Teodosije, arising from his thorough analysis of the historical facts in the works of these two writers.